دراسة تحليلية للعلاقة بين آليات حوكمة الشركات وتحقيق الشفافية في التقارير المالية للمصارف (دراسة ميدانية على المصارف التجارية السودانية) - محمد, عمر السر الحسن; خليلو, حسام عيسى (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تتمثل مشكلة البحث في ضعف اهتمام المصارف السودانية بآليات حوكمة الشركات لتحقيق الشفافية في التقارير المالية بالرغم من إلزام البنك المركزي لها بتطبيق حوكمة الشركات باعتبارها ضمان للإفصاح الكامل عن المعلومات المالية، هدفت البحث إلى بيان أثر آليات حوكمة الشركات في إضفاء الموثوقية في التقارير المالية من خلال تحقيق الشفافية في التقارير المالية لمصارف السودانية، واعتمدت البحث على الاستبانة كأداة لجمع البيانات، توصلت البحث إلى أن التنسيق بين آليات حوكمة الشركات يساعد على تلبية احتياجات مستخدمي المعلومات المحاسبية من خلال الشفافية في التقارير المالية للمصارف، وإشراك لجنة المراجعة في اختيار وتعيين المراجع الخارجي يضفي الموثوقية في التقارير المالية للمصارف التجارية السودانية، وأوصت البحث بضرورة التنسيق بين آليات حوكمة الشركات في المصارف السودانية لتلبية حاجات مستخدمي التقارير المالية، والعمل على إصدار تقرير عن فاعلية آليات حوكمة الشركات في المصارف السودانية لدعم الشفافية في التقارير المالية.The problem of the study is represented in the lack of interest of Sudanese banks in corporate governance mechanisms to achieve transparency in financial reports despite the fact that the central bank oblige them to apply corporate governance as to ensure full disclosure of financial information.The study aimed to demonstrate the impact of corporate governance mechanisms in giving reliability in financial reports by achieving transparency in financial reports of Sudanese banks.The Study depended on a questionnaire as a tool for data collection.The study found that coordination between corporate governance mechanisms helps to meet the needs of users of accounting information through transparency in financial reporting for the banks,Also it found that the involvement of the audit committee in the selection and appointment of the external auditor adds credibility in the financial reports of Sudanese commercial banks.The study recommended the need for coordination between corporate governance mechanisms in Sudanese banks to meet the needs of users of financial reports, also it recommended to work on issuing a report on the effectiveness of corporate governance mechanisms in Sudanese banks to support transparency in financial reporting.